2013
DOI: 10.1016/j.jstrokecerebrovasdis.2012.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Functional Outcome among Stroke Patients in Lima, Peru

Abstract: Background Due to the aging population in low- and middle-income countries, cerebrovascular disease is expected to remain a leading cause of death. Little has been published about stroke in Peru. Aims We conducted a retrospective cohort study of hospitalized stroke patients at a referral center hospital in Lima, Peru to explore factors associated with functional outcome among stroke patients. Methods We identified 579 patients hospitalized for ischemic stroke or intracerebral hemorrhage stroke at the Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 20 publications
0
20
0
6
Order By: Relevance
“…Furthermore, hospitalization length was significantly increased in older patients (>65 yrs) with stroke (Qureshi et al 2013). Observational studies in university-hospital settings reported that age was a highly significant predictor of poor functional outcome (Knoflach et al 2012, Denti et al 2010, Abanto et al 2013). Moreover, a small study of centenarians also confirmed that strokes were much more severe in this population than in other age groups (Olsen & Andersen 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, hospitalization length was significantly increased in older patients (>65 yrs) with stroke (Qureshi et al 2013). Observational studies in university-hospital settings reported that age was a highly significant predictor of poor functional outcome (Knoflach et al 2012, Denti et al 2010, Abanto et al 2013). Moreover, a small study of centenarians also confirmed that strokes were much more severe in this population than in other age groups (Olsen & Andersen 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Estos números varían en cuanto se refieren a mortalidad hospitalaria o al mes del evento, oscilando entre el 12% y el 33%. En nuestro medio, dos estudios mostraron que la mortalidad hospitalaria de pacientes con diagnóstico de ECV en un hospital público fue de aproximadamente de 20% en el periodo [2000][2001][2002][2003][2004][2005][2006][2007][2008][2009] (10) y de 5,2% en otro hospital de referencia en el periodo 2008-2009 (12) . No hay reportes de mortalidad en el seguimiento de pacientes con ECV en nuestro medio.…”
Section: Discussionunclassified
“…Está descrito que la funcionalidad de los pacientes que sobreviven tiende a mejorar (2,5,8,12) , ya sea por las sesiones de rehabilitación a la cual se somete a los pacientes o por selección natural, pues los sobrevivientes son los que mejor funcionalidad y pronóstico tienen de acuerdo con los presentes hallazgos. En este estudió también se halló mejoría al año.…”
Section: Discussionunclassified
See 2 more Smart Citations